Hydrodynamics in swimming - Ungerechts, B.; Arellano, R. (World book of swimming: From science to performance, 2012)
A swimmer needs solutions of propulsive actions to cover a given distance in least amount of time in aquatic space which is referred to as self-produccd propulsion. In aquatic space - in contrast to locomotion on land - the cyclic interaction between the body (and its parts) and water mass is essential to achieve propulsion. The water mass is displaced "irregularly" creating unsteady flow conditions. Since water mass is accelerated and decelerated, unsteady flow conditions are coming onto play, e.g. another force, called Accclcration-Reaction (AR) and vortex induced momentum. Momentum is propelling the body while forces are changing the propelling effects. AR can slow either down the swimmer or thrust the swimmer depending on the timing of body motion and motion of water. Vortex induced momentum in unsteady flow is based on fast turning actions of the body parts. This is best explained referring to aquatic animals: the trunk is displacing water and the tail and fin are accelerating the water mass resulting in vortex forms. Some vortex forms when accompanied by a jet-flow may result in additional thrust effects. PIV-methods [16, 22] or CFD-methods [9, 21, 24] allow for unsteady flow visualization and calculation of the momentum and forces due to self-propelling actions.